2013
DOI: 10.1017/s0142716413000301
|View full text |Cite
|
Sign up to set email alerts
|

Academic discourse: Dissociating standardized and conversational measures of language proficiency in bilingual kindergarteners

Abstract: This study examined the relationship between performance on standardized measures of language proficiency and conversational measures of the same features used in academic discourse among 24 monolingual and 25 bilingual kindergarteners. Academic discourse performance was considered for both its linguistic and its genre features in two discourse forms: narrative and explanation. Bilinguals performed more poorly than monolinguals on standardized measures of language proficiency, yet they performed similarly to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
2
9
0
1
Order By: Relevance
“…That is, whereas the standardized vocabulary assessment used in this study reflects children's knowledge of word labels, the measure of word diversity reflects children's productivity with language, specifically, skill in using words. Previous study findings also show asymmetrical performance by bilinguals on standardized and narrative-elicited vocabulary, albeit only assessed in English (Peets & Bialystok, 2015). Thus, we extend this previous literature by including a measure of bilinguals' Spanish skills, in addition to English skills, and providing evidence to support the view that narrative contexts may tap into an aspect of lexical development that is not measured by standardized assessments.…”
Section: Discussionsupporting
confidence: 75%
“…That is, whereas the standardized vocabulary assessment used in this study reflects children's knowledge of word labels, the measure of word diversity reflects children's productivity with language, specifically, skill in using words. Previous study findings also show asymmetrical performance by bilinguals on standardized and narrative-elicited vocabulary, albeit only assessed in English (Peets & Bialystok, 2015). Thus, we extend this previous literature by including a measure of bilinguals' Spanish skills, in addition to English skills, and providing evidence to support the view that narrative contexts may tap into an aspect of lexical development that is not measured by standardized assessments.…”
Section: Discussionsupporting
confidence: 75%
“…Nonetheless, there was no disadvantage for academic vocabulary among the bilingual group but, instead, lower scores only in vocabulary related to home life, most likely learned by children in their L1. These findings are in line with research that found that bilingual children are not disadvantaged in academic and literacy achievement (Bialystok et al 2005), nor in academic uses of spoken language (Peets and Bialystok 2015). Furthermore, when taken together, the bilingual children's vocabularies in their two languages could be larger than the vocabulary of monolingual children (Bialystok et al 2010).…”
Section: Lexical Knowledge Of Monolingual and Bilingual Childrensupporting
confidence: 89%
“…Arguably, since language production requires both language knowledge (e.g., vocabulary & syntax) and the engagement of executive control processes to manipulate these representations, bilingual executive control ability may compensate for poorer language proficiency. Work by Peets and Bialystok (in press) highlights the dissociation between formal measures of language proficiency and conversational measures. Peets and Bialystok found that although bilingual kindergarten students were less proficient in English than their monolingual counterparts according to standardized measures, analyses of bilinguals’ academic narratives revealed no differences in their vocabulary and grammar use.…”
Section: Discussionmentioning
confidence: 99%